Влияние мольного соотношения реагентов на кинетические параметры реакции 2,4,6-триметил-1,3,5-гексагидротриазин тригидрата с глиоксалем - Исакова, Кристина Александровна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25–28 апреля 2023 г.)
Imidazole and its derivatives have a wide range of applications. 2-methylimidazole (2MI) is a valuable epresentative of this class of compounds. The main method of obtaining 2-methylimidazole is the condensation in an aqueous solution of glyoxal, acetaldehyde, and ammonia. There is a lack of systematic study of kinetics in terms of the influence of reagents molar ratio on kinetic parameters. The kinetic parameters of this reaction have not been established. The current work is aimed at determining the influence of reagents molar ratio on rate constants and on initial reaction rates using NMR spectroscopy in situ with simultaneous monitoring of medium pH. The kinetic parameters of 2-methylimidazole formation were determined. It was established that there is the influence of the molar ratio of reagents, temperature, and medium pH on rate constants and on initial reaction rates. The NMR spectroscopy in situ was used for the first time for this class of reactions to monitor the concentrations of reactants and products.